Development of Interactive Learning Media Assisted by Padlet to Improve Concept Understanding on Regular Circular Motion Material in Class XI - Yulistia, Tri; Risdianto, Eko; Putri, Desy Hanisa; Kurniaty, Rikha (Kasuari: Physics Education Journal (KPEJ), 2024)
Technology in the learning process can improve education more effectively. This study aims to describe the feasibility of media and improve understanding of the concept of padlet on regular circular motion material. This type of research is research and development using the ADDIE model. The results of this development research include pre and post tests and validation by media experts (1) Padlet-assisted interactive learning media is considered very feasible with a percentage of 95.83% and an increase in understanding of the concept shown by 0.79 in the high category in the N-gain test (2) Based on the results of data analysis after using Padlet-assisted interactive learning media obtained a post-test percentage of 85.13%. It can be concluded that the interactive learning media assisted by Padlet is very feasible to use for regular circular motion material. In addition, the use of Padlet-assisted interactive learning media developed based on regular circular motion material, improves students' concept understanding.